Key to South American genera of Acanthocinini (Coleoptera, Cerambycidae, Lamiinae) without erect setae on elytra; synonymies, transferences, revalidation, and notes on genera with erect setae on elytra - Monné, Miguel A.; Santos-Silva, Antonio; Monné, Marcela L. (Zootaxa, 2020)
A key for identification for the 54 South American genera of Acanthocinini (Cerambycidae, Lamiinae) without erect setae on the elytra is provided. Diagnosis for each genus is provided, as well as type-locality and geographical distribution of the type species, and of the transferred species. Cristurges Gilmour, 1961 is considered a junior synonymy of Lophopoeum Bates, 1863. Ozineus Bates, 1863 is considered a genus that includes only the type species, Ozineus elongatus Bates, 1863 because it is the only species with erect setae on the elytral surface. Sternacutus Gilmour, 1961 is revalidated to include the species transferred from Ozineus. Nyssocuneus Gilmour, 1960 and Nyssodrysina Casey, 1913 are synonymized with Atrypanius Bates, 1864. Nyssodrysina Casey, 1913 is also considered a junior synonymy of Atrypanius. Nyssodectes Dillon, 1955 is considered junior synonymy of Stenolis Bates, 1864. Lepturguncus (Lepturguncus) Gilmour, 1961 is synonymized with Pattalinus Bates, 1881. Lepturdrys Gilmour, 1960 is considered a junior synonymy of Eucharitolus Bates, 1885. Lepturguncus (Chaeturguncus) is removed from the synonym of Pattalinus and considered a junior synonym of Paroecus Bates, 1863. The country of the type-locality of Oxathridia roraimae Gilmour, 1963 is corrected. The genus of Neseuterpia couturieri Tavakilian, 2001 is questioned. Additionally, the following genera omitted in the key by Monné et al. (2020) are listed and included in their previous key: Ozineus Bates, 1863; Paroecus Bates, 1863; Pseudosparna Mermudes & Monné, 2009; Probatiomimus Melzer, 1926; and Calolamia Tippmann, 1953. Paroectropsis Cerda, 1953 is transferred to Desmiphorini.